Pedagogical Approaches in Teaching Bachelor of Elementary Education Teacher-Candidates - Rio, Marites M.; Manimtim, Jannie SJ.; Aterrado, Johanne SJ. (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Study based on pedagogical approaches used by Bachelor of Elementary Education (BEE) teachers-candidates from College of Education, Rizal System University, Morong Campus. The findings revealed that BEE Teacher-Candidate Mentors made the most extensive use of collaborative and supportive approaches. The research underlines the significance of teachers’ disparities in teaching activities and students’ involvement in the learning process. The findings can be used to boost performance in the classroom and increase the students’ overall achievement